Decolonizing road safety for transportation justice in Australia - Johansen, Nadia; Wilson, Rohan; Tichon, Jennifer; Senserrick, Teresa; Tranter, Kieran (Transportation Research Part D: Transport and Environment, 2021)
Australia has a fundamental, deep, and enduring transport injustice. First Nations people endure road deaths and injury figures at vastly higher rates than the figure for non-First Nations people, suggesting that road safety research has not translated into successful policies and programs that sustainably reduce First Nations road trauma. In this paper, we argue that the decolonization of road safety research can only occur with First Nations people using culturally appropriate methodologies. We evaluate the scope and possibility of First Nations methodologies for decolonizing road safety, finding that yarning, or the ubiquitous use of conversation and storytelling to generate, pass on, and exchange knowledge, is a promising research methodology for decolonizing Australian road safety.